1998
DOI: 10.1034/j.1600-0412.1998.770407.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional stress of reproduction, A cohort study over two consecutive pregnancies

Abstract: The nutritional stress imposed by reproduction affects maternal and fetal outcomes. Maternal nutrient stores can be depleted and fetal growth can be restricted in association with shorter birth intervals. Perinatal nutrition may be improved by adequate spacing of pregnancies with appropriate birth control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…12 One hypothesis is that maternal nutritional depletion through close succession of pregnancies and lactations arising because of insufficient time for replenishment may increase the risk of adverse offspring outcomes. 19 For example, the lack of replenishment of the physiological depletion of folate that occurs in pregnancy and lactation may lead future pregnancies to be conceived under a state of folate deficiency, thereby increasing the risks of neural tube defects, fetal growth restriction, and preterm birth. 20…”
Section: Discussionmentioning
confidence: 99%
“…12 One hypothesis is that maternal nutritional depletion through close succession of pregnancies and lactations arising because of insufficient time for replenishment may increase the risk of adverse offspring outcomes. 19 For example, the lack of replenishment of the physiological depletion of folate that occurs in pregnancy and lactation may lead future pregnancies to be conceived under a state of folate deficiency, thereby increasing the risks of neural tube defects, fetal growth restriction, and preterm birth. 20…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies examined the association between birth spacing and maternal anthropometric outcomes (Greene et al 1988;Miller and Huss-Ashmore 1989;Merchant, Martorell, andHaas 1990a and1990b;Farahati, Bozorgi, and Luke 1993;Pebley and DaVanzo 1993;Winkvist et al 1994;Herman and Yu 1997;Khan, Chien, and Khan 1998). Three used interpregnancy interval, two used birth interval, three used recuperative interval, and one used both interpregnancy and recuperative interval as measures of birth spacing.…”
Section: Maternal Nutritional Depletionmentioning
confidence: 99%
“…Greene and colleagues (1988) and Merchant, Martorell, and Haas (1990a) found that long interpregnancy or recuperative intervals were associated with greater weight gain between pregnancies or with greater maternal anthropometric measures. Merchant, Martorell, and Haas (1990b) and Khan, Chien, and Khan (1998) reported that short recuperative or birth intervals were significantly associated with reduced maternal fat stores or with a negative change in postpartum maternal weight and body mass index.…”
Section: Maternal Nutritional Depletionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the adverse effects of short pregnancy intervals has not been established, but the leading theory involves the incomplete restoration of the mother's physiologically critical nutrient reserves that are depleted during the course of pregnancy (Khan et al 1998). …”
Section: Discussionmentioning
confidence: 99%